PRSPs : their significance for health : second synthesis report (WHO GenevaCH, 2004)
Presents an analysis of Poverty Reduction Strategy Papers (PRSPs) from a health perspective. Seeks to determine to what extent improved health is seen to play a role in poverty reduction. Examines to what extent the health component of a PRSP identiifies and proposes strategies to meet the specific health needs of poor people.
Keywords: POVERTY ALLEVIATION